Transformational Leadership, Training and Their Effects on Employee Engagement of Family Planning Fieldworkers in Indonesia - Wahidin Wahidin; Hamidah Hamidah; M. Rizal Martua Damanik; Arum Fitria (Journal of International Conference Proceedings (JICP), 2020)
The issuance of Law of the Republic of Indonesia Number 23 of 2014 concerning Regional Government has an extraordinary impact on the management of Human Resources at The National Population and Family Planning Board (BKKBN), which is The Family Planning Fieldworkers (PKB) that previously had been managed by the regency/city government, after the regulation, the management authority shifted to BKKBN. This study aims to analyze the effect of training variables on transformational leadership, the effect of training variables on employee engagement, and the influence of transformational leadership variables on employee engagement, and to analyze the effect of training variables on employee engagement through mediating the transformational leadership variable. This study used 397 respondents of The Family Planning Fieldworkers who were spread throughout Indonesia. This study used a questionnaire with references to existing theories accompanied by trials to determine the level of validity and reliability. To find out the relationship between variables, Structural Equation Modeling (SEM) analysis techniques are used which are operationalized through the LISREL program. The results showed: (1) The training conducted for Family Planning Fieldworkers had a significant effect on the Transformational Leadership variable, namely t count (7.66) > t table (1.96) with a coefficient value of 0.41; (2) The training given to Family Planning Fieldworkers has a statistically significant effect on employee engagement, namely t count (7.93) > t table (1.96), with a coefficient value of 0.50; (3) Transformational Leadership has a significant effect on employee engagement, namely t arithmetic (2.66) > t table (1.96), while the coefficient value is 0.14; (4) Training of Family Planning Fieldworkers significant effect on Employee Engagement through mediation of Transformational Leadership variables, which is obtained t value (2.72) > t table (1.96), while the coefficient value is 0.06.